Analysis of Interprofessional Factors (Integrity, Honesty, and Leadership) that Affect Nurse Performance: Literature Review - Lorenza Arinda Saputri Nur Endah Setyowati; Awanda Putra Pratama; Nadia Rosalinda; Najwa Tsaqifa ʻAzmil Umami; Shofa Zahrotun Naiim; Erianto Fanani; Ronal Surya Aditya (Ners Akademika, 2023)
Purpose: Nurses today must meet the pressure to make hospitals more competitive. The disconnect between corporate culture and improving nurse performance has been demonstrated in various studies. Although it is considered that organizational culture has a major impact on how well nurses work, it is still unclear how culture can improve nurse performance. To increase the effectiveness of health care facilities, a nurse must also be trustworthy and honest. This has had a significant impact on the way in which nurses provide medical care to patients. Therefore, although there have been previous interprofessional care studies, there has been no research that systematically explores interprofessional nursing factors which include three indicators, namely integrity, honesty, and leadership. This supports us in conducting a literature review which is expected to provide evidence that these three indicators have an important influence in improving the interprofessional abilities or capabilities of a nurse. Aim: To determine the factors that influence IPC in nurses which include integrity, honesty, and leadership. Methodology: For this article's research, ten literature reviews were used, and keyword syntax for each database was used to search PubMed, Google Scholar, and ResearchGate databases from 2018 to 2023. Results: The literature review shows how leadership, integrity, and honesty are factors influencing interprofessional nursing. From this comprehensive subject matter, the following sub-themes emerge: Integrity in Nurses with Other Professions, The Nature of Honesty in the Individual Nurses, Leading a Team with Leadership, and Nurse Performance IPC Conclusion: The ability of nurses to perform at their best in order to care for patients and enhance hospital performance is dependent on interprofessional attitudes such as integrity, honesty, and leadership.